From plants to patterns: Constructing a comprehensive online strontium isoscape for Belgium (IsoBel) using high density grid mapping - Amanda Sengeløv; Giacomo Capuzzo; Sarah Dalle; Hannah F. James; Charlotte Sabaux; Elisavet Stamataki; Marta Hlad; Carina T. Gerritzen; Emma M. Legrand; Barbara Veselka; Guy De Mulder; Rica Annaert; et al. (Geoderma)
Understanding the spatial distribution of strontium isotopes in plants or other archives within a region is crucial for various fields, including archaeology, environmental studies, food sciences and forensic science. This study aims to create a detailed dynamic strontium isoscape for Belgium through high-density plant sampling, presented in a web application (IsoBel) that serves the mentioned research fields. A total of 540 plant samples (199 locations), representing various species of grass, shrubs, and trees across Belgium were collected and were analysed for their strontium isotope ratios (87Sr/86Sr) to create a first biologically available strontium map. Sampling sites were selected to cover diverse lithological formations and soil types, ensuring representative coverage of the region’s geological heterogeneity, by using a novel high density grid mapping method. Sixty-four previously published plants from 21 locations are also included in this study, bringing the total amount of plant samples used to 604 from 220 locations. The results reveal significant variations in 87Sr/86Sr across Belgium (ranging from 0.7054 to 0.7259), which reflect the underlying lithology and geological processes (tectonics, weathering,…) which shaped the landscape. Although overlapping 87Sr/86Sr is seen across the majority of lithologies, there is a statistically significant difference between the distribution of 87Sr/86Sr values across all different lithological units in Belgium (Kruskal-Wallis test; p < 0.0001). Distinct regional patterns were observed, with higher 87Sr/86Sr in the older geological south-eastern part of Belgium, compared to the younger north-western parts. The high-density plant sampling approach employed in this study allowed for enhanced spatial resolution and improved accuracy in the predictive surfaces for bioavailable 87Sr/86Sr created by Empirical Bayesian Kriging (EBK). These findings provide valuable insights into the geographic distribution of strontium isotopes within Belgium and offer a foundation for future studies in archaeology, ecology, environmental studies, food sciences and forensics. Furthermore, the extensive coverage of various plant species provided a robust representation of the local ecosystems and their strontium sources. Overall, this study contributes to the growing body of knowledge on regional strontium isoscapes, enhancing our understanding of the complex interplay between litho- and biosphere in shaping the strontium isotope compositions of ecosystems.